MEASUREMENT OF TECHNICAL EFFICIENCY AND ITS DETERMINANTS IN COTTON PRODUCTION IN NORTH-WEST, NIGERIA (Proceedings of The International Conference on Economics and Development, 2017)
This study was designed to measure the technical efficiency and its determinants in cotton production in North West, Nigeria. The study used primary data generated during the 2013/2014 cotton production season. Data were collected through the use of structured questionnaire administered to 355 cotton farmers. The data were analyzed using stochastic frontier production model. Multi stage purposive sampling technique was used to select the States, the Agricultural Development Project zones, the Local Governments and the villages, while random sampling was used to select the respondents from which input-output data were collected. The result of the overall elasticities of production which give the level of return to scale derived from the Cobb-Douglas equation was 0.68. The result of the study further shows that 30% of the farmers had technical efficiency of 0.81 and above while 70% of the farmers operate at less than 0.8 efficiency level. The farmers with the best and least practice had a technical efficiency of 0.99 and 0.10, while the average technical efficiency index was 0.65 respectively. This implies that on the average, output fall by 35% from the maximum possible level due to inefficiency. The result of the determinants of technical inefficiency shows that the coefficients for age and farming experience were significant at 1%.level of probability, while educational level, household size and marital status were negative and not significant.
Keywords: Technical Efficiency; Determinants of Technical Inefficiency; Cotton Production